Approximately Quasi Inner Generalized Dynamics on Modules - M. Mosadeq (Journal of Sciences, Islamic Republic of Iran)
We investigate some properties of approximately quasi inner generalized dynamics and quasi approximately inner generalized derivations on modules. In particular, we prove that if A is a C*-algebra, is the generator of a generalized dynamics on an A-bimodule M satisfying and there exist two sequences of self adjoint elements in A such that for all in a core for , , then is approximately quasi inner.